Faktor Psikologis Sosial Dalam Meningkatnya Tingkat Agresivitas Dan Kejahatan Tindak Kekerasan Dikalangan Remaja - Shabrina Shabrina; Nafika Meisya putri; Dian Anggraini Rahmawati; Tiara Salsabilla; Tugimin Supriyadi (Concept: Journal of Social Humanities and Education, 2025)
The level of aggressiveness and violent crime among teenagers is increasing, with social psychological factors playing an important role in this phenomenon. This research aims to understand the root causes of aggres sive behavior in adolescents and its impact, in order to develop effective intervention strategies. Through literature study methods, this research collects, reads, records and analyzes objectively, systematically, analytically and critically the social and psychological impacts of aggressiveness among adolescents. Results from a review of several journals show that aggressive adolescent behavior is caused by various factors, including hormonal changes, brain development, family parenting, domestic violence, mental disorders, peer influence, and media exposure.